Pharmacovigilance of lower urinary tract adverse events among commonly prescribed medications: A FAERS database analysis - Robert Adler; Michael Kozlov; Mark M. Shimanov; Dylan S. Davie; Benjamin Mishail; David Musheyev; Jeffrey P. Weiss (Continence)
Background:: Lower urinary tract symptoms (LUTS) are a diverse group of urologic conditions characterized by dysfunction in storage, voiding, and post-micturition control. Previous studies estimate that medications account for 10% of LUTS in men. Pharmacovigilance studies, such as those using the Food and Drug Administration (FDA) Adverse Events Reporting System (FAERS), aid physicians in identifying adverse reactions and potential mechanisms to improve clinical practice. Our study sought to identify drugs that are potentially associated with LUTS and investigate the relationship between a variety of commonly prescribed medications and various LUTS. Methods:: The FAERS Database was queried for a list of 17 Reaction Terms. Proportion of drug reactions to total and proportional reporting ratios were calculated for each drug. FDALabel was used to determine whether any LUTS were within the side effect profile of a drug. Results:: LUTS accounted for .8% of total adverse reactions. Mirabegron (14.39) had the highest proportion of LUTS events compared to all adverse events, followed by Tolterodine Tartrate (10.95) Fesoterodine Fumarate (7.20), Tamsulosin Hydrochloride (7.07), and Warfarin Sodium (6.46). Other classes such as immunotherapeutics, proton pump inhibitors, and various psychiatric medications reported LUTS that were not within the FDALabel. Conclusion:: Medications causing LUTS encompass a wide variety of classes. We discovered several medications for which FDA labels were inconsistent with reporting of adverse events. Physicians should be aware of potential medications that have not been previously reported to cause LUTS or do not contain specific LUTS within their FDA label.